1982
DOI: 10.1021/bi00258a001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of castration on the synthesis of seminal vesicle secretory protein IV in the rat

Abstract: The effects of castration on the synthesis (accumulation) of a major seminal vesicle secretory protein (SVS IV) were examined in young adult rats. In vitro incorporation of labeled amino acids into SVS IV by minced tissue was monitored by immunological methods. Castration resulted in a large decrease in the differential synthesis of SVS IV. A significant decrease in the relative incorporation of isotope into SVS IV was evident within 3 days of castration, and by 4 weeks relative incorporation dropped some 30-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Also, the possibility that PN-I mRNA processing or stability might be affected by androgens should be considered (Higgins and Hemingway, 1991). The rodent seminal vesicle has long been known to be exquisitely sensitive to the androgenic status of the animals, and a number of its secretory products have been shown to be under testosterone control (Ostrowski et al, 1982;Brooks et al, 1986;Chen et al, 1987;Mills et al, 1987;Schifman et al, 1988;Harris et al, 1990;Higgins and Hemingway, 1991). A comparison of the genes coding for these different products, which now include PN-I, should yield valuable information regarding the mechanism of androgen regulation in the male genital tract.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the possibility that PN-I mRNA processing or stability might be affected by androgens should be considered (Higgins and Hemingway, 1991). The rodent seminal vesicle has long been known to be exquisitely sensitive to the androgenic status of the animals, and a number of its secretory products have been shown to be under testosterone control (Ostrowski et al, 1982;Brooks et al, 1986;Chen et al, 1987;Mills et al, 1987;Schifman et al, 1988;Harris et al, 1990;Higgins and Hemingway, 1991). A comparison of the genes coding for these different products, which now include PN-I, should yield valuable information regarding the mechanism of androgen regulation in the male genital tract.…”
Section: Resultsmentioning
confidence: 99%
“…The insert size together with the result of the hybridization of insert fragments to 32P-cDNA probes and the sequencing data prove that the insert corresponds to an almost full-length structural gene coding for a precursor to SVS protein IV. It is well established that the synthesis of SVS protein IV is controlled by testosterone (4). In this report we have used the cloned structural gene to determine the concentration of mRNAIV after administration of testosterone to rats castrated for five weeks.…”
Section: Testosterone Induction Of Mrna Svs IVmentioning
confidence: 99%
“…SVS protein IV has been described (1,2,3,4) and the amino acid sequence has been deduced (13). The biological function of protein IV is still unknown but considering that this protein represents 25-30% of the seminal vesicle protein-synthetic output an important role in reproduction seems very likely.…”
Section: Testosterone Induction Of Mrna Svs IVmentioning
confidence: 99%
See 1 more Smart Citation
“…The rat seminal vesicle secreted protein SVSIV and SVSV are small (-10 kDa) androgen-regulated proteins [9,10]. They are expressed from genes that are organized in a way similar to the semenogelin (Sg) genes, with one exon encoding the signal peptide, a second encoding the secreted protein and a third encompassing 3' non-translated nucleotides [11,12] It has previously been shown that the 3' non-translated nucleotides of cDNAs for human SgI and rat SVSIV are similar in sequence [7].…”
Section: Introductionmentioning
confidence: 99%